2008
DOI: 10.1093/annhyg/men005
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Performance Offered by N95 Respirators and Surgical Masks: Human Subject Evaluation with NaCl Aerosol Representing Bacterial and Viral Particle Size Range

Abstract: The study indicates that N95 filtering facepiece respirators may not achieve the expected protection level against bacteria and viruses. An exhalation valve on the N95 respirator does not affect the respiratory protection; it appears to be an appropriate alternative to reduce the breathing resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
213
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(229 citation statements)
references
References 24 publications
9
213
1
6
Order By: Relevance
“…The relationship between particle size and PF obtained in our study is corroborated by the findings in previous studies (Lee et al , 2008; Cho et al , 2010). The PF values for eight different particle size ranges between 40 to 1200 nm were measured for N95 FFRs worn by human subjects (Lee et al , 2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The relationship between particle size and PF obtained in our study is corroborated by the findings in previous studies (Lee et al , 2008; Cho et al , 2010). The PF values for eight different particle size ranges between 40 to 1200 nm were measured for N95 FFRs worn by human subjects (Lee et al , 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, PF for N95 FFRs worn by subjects was measured as a ratio of particle concentration outside to inside the respirator in a controlled test chamber, using an Electrical Low Pressure Impactor (ELPI) (Lee et al , 2008). The ELPI measures the particle concentration of different aerodynamic diameter size particles.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 , 15 ] Results showed that the number of test subjects passing the TIL test (i.e., TIL <1.0%) was significantly lower in the laboratory with a CMD of 82 nm compared to the laboratory with a CMD of 131 nm indicating the effect of particle size distribution on TIL measurement. [ 8 ] The results are consistent with the findings in other studies, [ 12 , 13 ] which showed a particle size-dependent increase in protection factor (inverse factor of TIL). Recent studies also showed TIL was particle size-dependent for different types of aerosols.…”
Section: Introductionsupporting
confidence: 91%
“…Some older studies have reported variable effectiveness against viral and bacteria-sized particles (Chen & Willeke 1992;Weber et al 1993;Chen et al 1994). Even though the materials, methods and mask designs may have changed since then, later studies on N95 masks still show variable effectiveness against viral and bacteria-sized particles (Qian et al 1998, Lee et al 2008, Johnson et al 2009). Second, the actual act of wearing masks and keeping them on in a proper position is very difficult, as multiple studies on healthcare workers (who wear masks to protect themselves from patients and patients from themselves) have shown (CDC 2009;Jacobs et al 2009, Seale et al 2009, Gershon et al 2009).…”
Section: Mitigating Transmissionmentioning
confidence: 99%